Evidence that ageing does not influence the uniformity of the muscle–tendon unit adaptation in master sprinters. (7th May 2021) - Epro, G.; König, M.; James, D.; Lambrianides, Y.; Werth, J.; Hunter, S.; Karamanidis, K.
Abstract: Differences in the adaptation processes between muscle and tendon in response to mechanical loading can lead to non-uniform mechanical properties within the muscle–tendon unit (MTU), potentially increasing injury risk. The current study analysed the mechanical properties of the triceps surae (TS) MTU in 10 young (YS; 22 ± 3 yrs) and 10 older (OS; age 65 ± 8 yrs; i.e. master) (inter)national level sprinters and 11 young recreationally active adults (YC; 23 ± 3 yrs) to detect possible non-uniformities in muscle and tendon adaptation due to habitual mechanical loading and ageing. Triceps surae muscle strength, tendon stiffness and maximal tendon strain were assessed in both legs during maximal voluntary isometric plantarflexion contractions via dynamometry and ultrasonography. Irrespective of the leg, OS and YC in comparison to YS demonstrated significantly ( P  < 0.05) lower TS muscle strength and tendon stiffness, with no differences between OS and YC. Furthermore, no group differences were detected in the maximal tendon strain (average of both legs: OS 3.7 ± 0.8%, YC 4.4 ± 0.8% and YS 4.3 ± 0.9%) as well as in the inter-limb symmetry indexes in muscle strength, tendon stiffness and maximal tendon strain (range across groups: –5.8 to 4.9%; negative value reflects higher value for the non-preferred leg). Thus, the findings provide no clear evidence for a disruption in the TS MTU uniformity in master sprinters, demonstrating that ageing tendons can maintain their integrity to meet the increased functional demand due to elite sports.